2020
DOI: 10.1017/s0007114520001956
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2′-fucosyllactose and galacto-oligosaccharides on the growth and adhesion of Streptococcus mutans

Abstract: Abstract Human milk oligosaccharides, such as 2′-fucosyllactose (2′-FL), and galacto-oligosaccharides (GOS), a prebiotic carbohydrate mixture, are being increasingly added to infant formulas, necessitating the understanding of their impact on the oral microbiota. Here, for the first time, the effects of 2′-FL and GOS on the planktonic growth and adhesion characteristics of the caries-associated oral pathogen Streptococcus mutans were assessed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
(87 reference statements)
1
15
0
Order By: Relevance
“…Previous studies indicated that 2′-FL had growth-inhibiting and adhesion-reducing effects on certain microorganisms [ 25 , 26 ], and thereby the tolerance of B. subtilis to 2′-FL needs to be examined. B. subtilis was cultured in LB medium containing different concentrations of 2′-FL with 96-well plates.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that 2′-FL had growth-inhibiting and adhesion-reducing effects on certain microorganisms [ 25 , 26 ], and thereby the tolerance of B. subtilis to 2′-FL needs to be examined. B. subtilis was cultured in LB medium containing different concentrations of 2′-FL with 96-well plates.…”
Section: Resultsmentioning
confidence: 99%
“…Infant oral microbiota are important for oral health [ 79 ] and differences in the oral microbiota between breastfed and formula-fed infants have been reported [ 91 , 95 , 96 ], however, little is known about how HMOs impact the oral microbiota. A recent in vitro study assessed the effect of 2′FL and galacto-oligosaccharides on the growth and adhesion characteristics of the caries-associated oral pathogen Streptococcus mutans and reported 2′FL both limits growth and inhibits adhesion of S. mutans to saliva-coated hydroxyapatite [ 97 ]. However, there is an absence of information on how daily intakes of HMOs influence infant oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on the growth and adhesion of Streptococcus mutans found that GOS promoted the growth of Streptococcus mutans as a carbon source, while 2′-FL could not. Both could reduce the adhesion of pathogenic bacteria, but the mode of inhibition might be different [ 30 ]. Previous studies in our laboratory confirmed that 2′-FL intervention could regulate the composition of the gut microbiota, and the colonization of E. coli O157 in the intestines of mice was decreased by over 90%.…”
Section: Introductionmentioning
confidence: 99%